2016
DOI: 10.1242/jcs.180737
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ is a key factor in α-synuclein-induced neurotoxicity

Abstract: Aggregation of α-synuclein leads to the formation of oligomeric intermediates that can interact with membranes to form pores. However, it is unknown how this leads to cell toxicity in Parkinson's disease. We investigated the species-specific effects of α-synuclein on Ca2+ signalling in primary neurons and astrocytes using live neuronal imaging and electrophysiology on artificial membranes. We demonstrate that α-synuclein induces an increase in basal intracellular Ca2+ in its unfolded monomeric state as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 25 publications
9
138
0
1
Order By: Relevance
“…Calcium is the most pleiotropic ion that is capable of triggering intracellular pathways in response to external stimuli [5,63,64]. We have reported that a-syn oligomers induce cytosolic calcium influx in neurons, and this results in an increase in cytosolic calcium before inducing cell death; cell toxicity is rescued by exclusion of extracellular calcium [5], confirming the importance of oligomer-induced membrane disruption in inducing neuronal toxicity. We have reported that a-syn oligomers induce cytosolic calcium influx in neurons, and this results in an increase in cytosolic calcium before inducing cell death; cell toxicity is rescued by exclusion of extracellular calcium [5], confirming the importance of oligomer-induced membrane disruption in inducing neuronal toxicity.…”
Section: Membrane Disruption and Calcium Dysregulationmentioning
confidence: 73%
See 2 more Smart Citations
“…Calcium is the most pleiotropic ion that is capable of triggering intracellular pathways in response to external stimuli [5,63,64]. We have reported that a-syn oligomers induce cytosolic calcium influx in neurons, and this results in an increase in cytosolic calcium before inducing cell death; cell toxicity is rescued by exclusion of extracellular calcium [5], confirming the importance of oligomer-induced membrane disruption in inducing neuronal toxicity. We have reported that a-syn oligomers induce cytosolic calcium influx in neurons, and this results in an increase in cytosolic calcium before inducing cell death; cell toxicity is rescued by exclusion of extracellular calcium [5], confirming the importance of oligomer-induced membrane disruption in inducing neuronal toxicity.…”
Section: Membrane Disruption and Calcium Dysregulationmentioning
confidence: 73%
“…Furthermore, once oligomers are formed, they are able to disrupt membranes and this is due to their structural composition, with a high lipophilic component promoting membrane interaction, and the cross b-sheet structure leading to integration into the lipid bilayer [62]. Calcium is the most pleiotropic ion that is capable of triggering intracellular pathways in response to external stimuli [5,63,64]. Calcium is the most pleiotropic ion that is capable of triggering intracellular pathways in response to external stimuli [5,63,64].…”
Section: Membrane Disruption and Calcium Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cell cocultures of neurons and astrocytes were prepared as described in detail previously (Angelova, Ludtmann, et al, 2016; Turovsky et al, 2016) with modifications, from the midbrains and cerebral cortices of Sprague‐Dawley P3 rat pups or wildtype and LRRK2 knockout C57BL/6 mice (UCL breeding colony). Experimental procedures were performed in compliance with the United Kingdom Animals (Scientific Procedures) Act of 1986.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, secreted α-syn induced an increase in capacitive Ca(II) entry in differentiated SH-SY5Y cells (Melachroinou et al, 2013). Transmembrane entry of Ca(II) or other cations may be via α-syn pore-like oligomers (Pountney et al, 2005; Mironov, 2015) and can mediate cytotoxicity (Angelova et al, 2016). Transgenic mice over-expressing human WT α-syn showed that α-syn transgenic mice exhibited augmented, long-lasting Ca(II) transients characterized by considerable deviation from the exponential decay.…”
Section: α-Synuclein Aggregation Raised Ca(ii) and Oxidative Stressmentioning
confidence: 99%